A Critique on the Book Three Rival Versions of Modernity: Exit, Voice, Loyalty - Salman Sadeghizadeh (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
By now many have considered modernity as an integrated totality that was born and flourished in a given time and in a given location. From this point of view, modernity is incompatible and alien to other territories and cultures, but if we consider modernity as a “cultural text” creating a suitable context for human subjectivity, then we would know it as an omnipresent phenomenon in all the human aggregations. The book Three Rival Versions of Modernity: Exit, Voice, and Loyalty focuses on incompatibilities in understanding modern affairs. Hence it shows the different capabilities inside modernity. Therefore, the central problem of the book has to do with the way of approaching modernity. Though the main part of the book is dedicated to the analysis of six Western thinker’s theories, the last part focuses on Iranian thinkers and analyses their attitudes toward modernity from three different standpoints: exit, voice, and loyalty. Finally, the book could be considered as a precious effort in understanding modernity, which per se could lead Iranian society to adopt a more conscious approach in case of modernity.